The prevalence and associated disability burden of mental disorders in children and adolescents in China: a systematic analysis of data from the Global Burden of Disease StudyResearch in context - Wanyue Dong; Yunning Liu; Ruhai Bai; Lei Zhang; Maigeng Zhou (The Lancet Regional Health. Western Pacific)
Summary: Background: Understanding the disease burden of mental disorders in children and adolescents in China, especially at the sub-national level, is important for effective prevention and intervention. This study aims to assess the prevalence and related health burden of mental disorders in children and adolescents in China. Methods: Following the same approach as the Global Burden of Disease Study 2021, we systematically analyze epidemiological and demographic information for mental disorders, and assess the prevalence, disability-adjusted life-years (DALYs), and years lived with disability (YLDs) in the children and adolescents for mental disorders and their ten subtypes across national and provinces in China from 1990 to 2021. Findings: In 2021, the age-standardized prevalence of mental disorders in children and adolescents was 8.9% (uncertainty intervals [UI]: 8.1, 9.8) in China, accounting for 30.8 million cases (26.0, 36.3) and 2.8 million DALYs (2.0, 3.7). Among mental disorders, attention-deficit/hyperactivity disorder had the highest age-standardized prevalence, at 3.6% (3.0, 4.5). From 1990 to 2021, the age-standardized prevalence increased by 4.8%, but the number of mental disorders cases decreased by 21.9%. DALYs for mental disorders are higher in boys than in girls across all age groups. At the provincial level, the age-standardized prevalence of mental disorders in some provinces was much greater than that in other provinces (e.g., bipolar disorder in Hebei was more than two times greater than that in other provinces). Although disparities in the distribution of mental disorder burden were observed across provinces, there was a reduction in income-related inequality, where the gap in the age-standardized DALY rates between the highest and lowest income provinces decreased by 61.7% between 1990 and 2021. In 2021, among 22 health condition groups in China, mental disorders accounted for the largest proportion of health life lost. Interpretation: Mental disorders are the leading causes of disability in children and adolescents in China, and the disease burden varies geographically. Careful planning of health services, including consideration of the local situation, is needed. Funding: China National Natural Science Foundation (Grant No. 72104113, 72204112), Social Science Fund of Jiangsu Province (Grant No. 21GLD008), ShuangChuang Doctor Program of Jiangsu Province (Grant No. JSSCBS20210359), and the Fundamental Research Funds for the Central Universities (Grant No. 30923011101).